Highly efficient isolation of Populus mesophyll protoplasts and its application in transient expression assays. - Jianjun Guo (Public Library of Science (PLoS), 2012)
Background Populus is a model woody plant and a promising feedstock for lignocellulosic biofuel production. However, its lengthy life cycle impedes rapid characterization of gene function. Methodology/principal findings We optimized a Populus leaf mesophyll protoplast isolation protocol and established a Populus protoplast transient expression system. We demonstrated that Populus protoplasts are able to respond to hormonal stimuli and that a series of organelle markers are correctly localized in the Populus protoplasts. Furthermore, we showed that the Populus protoplast transient expression system is suitable for studying protein-protein interaction, gene activation, and cellular signaling events. Conclusions/significance This study established a method for efficient isolation of protoplasts from Populus leaf and demonstrated the efficacy of using Populus protoplast transient expression assays as an in vivo system to characterize genes and pathways.